Analysis of BLDC Motor Performance Under Varying Load Conditions in Four Wheel Electric Vehicles - Agrawal, Chinmay; Kumar Thakur, Manish; Prajapati, Amit; Janm Singh, Ram; Sahu, Harsh; Sharma, Kratika; Singh, Preeti (Journal of Neonatal Surgery, 2025)
This paper studies one of the significant parameters for electric vehicle (EV) performance under varying load conditions affected by real terrains. The work combines analytical models with on-ground testing, using a student-fabricated EV model to measure the effects of road conditions on torque-speed balance and total motor efficiency. Using a mechanical tachometer to measure rotating speed and MATLAB for data analysis, a brushless direct current (BLDC) motor was tested under increasing mechanical loads. Results show an inverse relationship between load and rotational speed. The gap between hypothetical simulations and real-life results emphasizes on the necessity for practical testing techniques. The research provides open-access datasets and an affordable method that promotes the design of energy-efficient motors that can handle variable load situations. This research promotes to improve electric vehicle technology, motor stability and overall optimisation of vehicle performance under various driving conditions.